2012
DOI: 10.1016/j.meatsci.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Quality traits and lipid composition of meat from Nellore young bulls fed with different oils either protected or unprotected from rumen degradation

Abstract: The qualitative characteristics, lipids and chemical composition of the meat of 35 Nellore young bulls were analyzed. These bulls had an average slaughter weight and fat thickness of 532.17±30.2 kg, and 7.00 mm, respectively. Significant differences were found only in the meat's water holding capacity (WHC), which was higher for animals fed with fresh linseed oil. More conjugated linoleic acid (CLA) was found in the meat of animals fed with unprotected soybean oil, while better omega-6/omega-3 ratios were note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
54
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 27 publications
19
54
4
3
Order By: Relevance
“…Different sources of lipid supplementation at 2% in the diet did not alter meat colour and this agrees with the findings from lambs fed fish oil or protected sunflower meal supplements (Ponnampalam, Trout, Sinclair, Egan, & Leury, 2001) or in bulls fed different sources of dietary fat (Oliveira et al, 2012). Priolo, Micol, and Agabriel (2001) suggested that changes in meat colour are usually associated with differences in fat content, carcass fatness or ultimate pH.…”
Section: Meat Quality Attributessupporting
confidence: 86%
See 1 more Smart Citation
“…Different sources of lipid supplementation at 2% in the diet did not alter meat colour and this agrees with the findings from lambs fed fish oil or protected sunflower meal supplements (Ponnampalam, Trout, Sinclair, Egan, & Leury, 2001) or in bulls fed different sources of dietary fat (Oliveira et al, 2012). Priolo, Micol, and Agabriel (2001) suggested that changes in meat colour are usually associated with differences in fat content, carcass fatness or ultimate pH.…”
Section: Meat Quality Attributessupporting
confidence: 86%
“…Given that all diets in the present study were balanced for vitamins and minerals with low levels (2%) of fat supplementation, one would expect no changes in meat colour due to different sources of fat supplementation. There were no significant (p > 0.05; Table 4) differences in cooking loss and shear force value among treatments which agree with the results of studies in beef where different sources of dietary fat were compared (Oliveira et al, 2012;Scheeder et al, 2001).…”
Section: Meat Quality Attributessupporting
confidence: 86%
“…This finding was not confirmed when the supplement was fed to cattle offered a high concentrate ration, which most likely reflects the different basal ration in both studies rather than the protection itself. Oliveira et al (2012) reported an increase in 18:2n−6 in bovine muscle when soyabean oil was replaced by a commercial product based on calcium salts of soyabean oil. An experimental version of this process applied to linseed oil however, did not protect 18:3n− 3 from ruminal biohydrogenation .…”
Section: Protected Lipidsmentioning
confidence: 99%
“…According to Oliveira et al (2012), CL values can be influenced by WHC, which is considered a very important trait for consumption, where in low values are related to a lower nutritional value, resulting in drier and less tender meat.…”
Section: Resultsmentioning
confidence: 99%